2011
DOI: 10.3174/ajnr.a2584
|View full text |Cite
|
Sign up to set email alerts
|

Parent Vessel Size and Curvature Strongly Influence Risk of Incomplete Stent Apposition in Enterprise Intracranial Aneurysm Stent Coiling

Abstract: BACKGROUND AND PURPOSE:Flexible microstents, such as the closed-cell EN, have facilitated adjunctive coiling of intracranial aneurysms. Little data are available on the ability of the stent struts to maintain vessel-wall apposition once deployed in the tortuous cerebral vasculature and the prevalence of ISA. The purpose of this study was to evaluate the relationship between geometric features of the parent vessel at the stent deployment site and prevalence of ISA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 22 publications
3
60
1
Order By: Relevance
“…Evaluation of the relationship between geometric features of the parent vessel at the stent deployment site and the prevalence of ISA detected a unique crescent flow pattern on 3 T magnetic resonance angiography, which was confirmed by flat panel computed tomography as indicating ISA. 7) Further multivariate analysis revealed that the crescent flow pattern correlated with small vessel-curvature radius, large stent-subtended angle, and large parent vessel diameter. 7) Two patterns of ISA of the Enterprise VRD were also reported in an in vitro stent deployment study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the relationship between geometric features of the parent vessel at the stent deployment site and the prevalence of ISA detected a unique crescent flow pattern on 3 T magnetic resonance angiography, which was confirmed by flat panel computed tomography as indicating ISA. 7) Further multivariate analysis revealed that the crescent flow pattern correlated with small vessel-curvature radius, large stent-subtended angle, and large parent vessel diameter. 7) Two patterns of ISA of the Enterprise VRD were also reported in an in vitro stent deployment study.…”
Section: Discussionmentioning
confidence: 99%
“…7) Further multivariate analysis revealed that the crescent flow pattern correlated with small vessel-curvature radius, large stent-subtended angle, and large parent vessel diameter. 7) Two patterns of ISA of the Enterprise VRD were also reported in an in vitro stent deployment study. 6) Using a microcatheter pull-back technique, the stents tended to follow the contour of the inner vessel curve, with poor contact on the outer curve (outer curve ISA).…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used method involves the initial placement of the microcatheter for coil delivery into the aneurysm and jailing of the catheter against the vessel wall by stenting. Despite increasing clinical experience and technological improvements, stent-assisted coiling still has inherent risks of morbidity and mortality [4][5][6][7] . The pirin daily for three to five days before treatment.…”
Section: %-99%) and 31% (95%ci 0%-73%) Combined Procedure-relatmentioning
confidence: 99%
“…Heller et al 16) reported that incomplete stent apposition of ES was associated with stent-subtended arc angle or parent vessel diameter. In our study, patients with a high risk of incomplete stent apposition located in an acute angle structure (e.g., carotid siphon) or within a small diameter parent artery were excluded, because incomplete stent apposition and delayed arterial healing was associated with delayed ischemic events and late stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Heller et al 16) evaluated for incomplete stent apposition using high-resolution flat-panel computed tomography (CT).…”
Section: Discussionmentioning
confidence: 99%